Impacts of tidal stream power on energy system security: An Isle of Wight case study. (15th March 2023) - Coles, Daniel; Wray, Bevan; Stevens, Rob; Crawford, Scott; Pennock, Shona; Miles, Jon
Abstract: The new Energy System Model for Remote Communities ( EnerSyM-RC ) is implemented to quantify impacts from adopting tidal stream power alongside solar PV, offshore wind and energy storage in the Isle of Wight energy system. Based on scenarios with gross renewable energy generation matched to projected annual demand (equivalent to 136 MW mean power), installing 150 MW of solar PV, 150 MW of offshore wind, and 120 MW of tidal stream capacity enhances supply–demand balancing whilst also reducing the magnitude of maximum power surplus, both by 25% relative to the best performing solar+wind system. Tidal stream adoption also reduces total land/sea space by 33%. The economic viability of tidal stream capacity adoption is heavily dependent on the price of reserve energy; when the reserve energy price exceeds the average 2022 forward delivery contracts price (250 £/MWh), adopting tidal stream capacity reduces the levelised cost of whole-system energy relative to solar+wind systems. This tipping point, at which the whole-system levelised cost of energy is 92 £/MWh, occurs when the premium on tidal stream energy is outweighed by savings on reserve energy. In general these system benefits arising from tidal stream adoption are consistent over a range of different demand profiles, and in cases where gross annual renewable supply is oversized relative to demand. Highlights: EnerSyM-RC model quantifies impacts of tidal stream (TS) on energy system security. Adoption of TS reduces reliance on reserve supply by 26%. TS limits maximum power surplus magnitude by 24%. TS reduces the total land/sea space used by renewables by 33%. TS minimises system LCoE to 92 £/MWh, with 250 £/MWh reserve energy price.